Trois sonates pour le pianoforte composées et dédiées à J. Haydn par L. van Beethoven.; No. I [ i.e. III]; Oeuv. 2 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Hamburg; A. Cranz; Germany, 2022)
Early edition of the Piano Sonata no. 3 in C major, op. 2, no. 3, published by A. Cranz in Hamburg. Lacks metronome markings or other editorial additions.